Mechanical Response of Shallow Crust to Groundwater Storage Variations: Inferences From Deformation and Seismic Observations in the Eastern Southern Alps, Italy. Issue 2 (16th February 2021) - Pintori, Francesco; Serpelloni, Enrico; Longuevergne, Laurent; Garcia, Alexander; Faenza, Licia; D'Alberto, Lucio; Gualandi, Adriano; Belardinelli, Maria Elina
Abstract: Changes in continental water storage generate vertical surface deformation, induce crustal stress perturbations, and modulate seismicity rates. However, the degree to which regional changes in terrestrial water content influence crustal stresses and the occurrence of earthquakes remains an open problem. We show how changes in groundwater storage, computed for a ∼1, 000 km 2 basin, focus deformation in a narrow zone, causing large horizontal, nonseasonal displacements. We present results from a karstic mountain range located at the edge of the Adria‐Eurasia plate boundary system in Northern Italy, where shortening is accommodated across an active fold‐and‐thrust belt. The presence of geological structures with high permeabilities and of deeply rooted hydrologically active fractures focus groundwater fluxes and pressure changes, generating transient surface horizontal displacements up to 5 mm and perturbations of crustal stress up to 25 kPa at seismogenic depths. The background seismicity rates appear correlated, without evident temporal delay, with groundwater storage changes in the hydrological basin. With no evidence of pore pressure propagation from the hydrologically active fractures, seismicity modulation is likely affected by direct stress changes on faults planes. Plain Language Summary: The natural water cycle, by changing how water is stored on the continents, can cause nonnegligible deformation at the Earth's surface. Redistribution of water masses has long been known to alter the state of stress in the crust and potentially modulate seismicity rates. However, the degree to which regional changes in groundwater storage influence crustal stresses and the occurrence of earthquakes at fault scales remains an open problem. We study a karst area located in a tectonically active region of Northern Italy, where plate convergence is accommodated across a complex system of faults and folds. We use GPS, hydrological, meteorological and seismological observations, integrated by hydrological and mechanical models, to show that there is a direct elastic connection between changes in groundwater storage, crustal deformation, and seismicity rates. We show that hydrologically active fractures and seismically active fractures might be disjoint, and that pore pressure propagation is not required to generate stress changes at seismogenic depths. Indeed, the convergence of water from upstream catchment toward permeable fractures connected to the surface can generate large pressure changes on the wall of these fractures, causing horizontal displacements and perturbations of the crustal stress that modulate background seismicity rates. Key Points: Regional groundwater storage changes in heterogeneous media modulate horizontal transient deformation Water pressure changes in shallow permeable fractures cause large elastic stress changes at seismogenic depth Background seismicity rates are correlated with groundwater storage changes